Social Capital and Family Resilience to The Pandemic: A Systematic Review in the Contemporary World - Zulkifli; Nuryaman; Zulkifli, Dhea Urfina; Fahri, Muhamad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The management of large-scale societal crises is often impeded by a complex interplay of factors, yet the strategic role of social capital in mitigating such unforeseen global challenges remains inadequately conceptualized. This study aims to systematically examine the contribution of social constitutive capital to the development of family resilience during the pandemic in the contemporary world. Employing a Systematic Literature Review (SLR) methodology, this research analyzed 20 pertinent articles sourced from the Scopus database. The results delineate a multifaceted typology of contributions: social capital functions through direct mechanisms, as a mediating variable alongside other factors, and through indirect pathways. The analysis establishes that social capital (operationalized through trust, networks, norms, and social organization) served as a fundamental pillar of family resilience. Its efficacy was significantly amplified when synergized with local belief systems, technological adoption, entrepreneurial initiatives, and institutional support. Furthermore, social capital acted as a critical mediator in enhancing relational capacities within marginalized demographics. A cross-national analysis of 27 countries highlighted the pivotal role of social trust in alleviating psychological distress, thereby bolstering collective resilience. Conversely, the study also revealed that the impact of social capital on individual resilience was comparatively less significant than that of socioeconomic status, demographic vulnerability, and robust physical infrastructure. These findings provide a seminal framework for understanding the multidimensional utility of social capital in crisis response.